The ON Crossover Circuitry Shapes Spatiotemporal Profile in the Center and Surround of Mouse OFF Retinal Ganglion Cells - Sabharwal, Jasdeep; Seilheimer, Robert L.; Cowan, Cameron S.; Wu, Samuel M. (Frontiers in Neural Circuits, 2016)
Retinal ganglion cells (RGCs) are often grouped based on their functional properties. Many of these functional properties, such as receptive field size, are driven by specific retinal circuits. In this report, we determined the role of the ON bipolar cell mediated crossover circuitry in shaping the center and surround of OFF RGCs. We recorded from a large population of mouse RGCs using a multielectrode array while pharmacologically removing the ON-bipolar cell-mediated crossover circuit. OFF sustained and transient responses to whole field stimuli are lost under scotopic conditions, but maintained under photopic conditions. Though photopic light responses were grossly maintained, we found that photopic light response properties were altered. Using linear receptive field mapping, we found a significant reduction in the antagonistic surround and a decrease in size of the receptive field center. Using a novel approach to separate the distinct temporal filters present in the receptive field center, we see that the crossover pathway contributes specifically to the sluggish antagonistic filter in the center. These results provide new insight into the role of crossover pathways in driving RGCs and also demonstrate that the distinct inputs driving the receptive field center can be isolated and assayed by RGC activity.